Lichen sclerosus and atopy in boys: coincidence or correlation? - Becker, Karl; Meissner, V.; Farwick, W.; Bauer, R.; Gaiser, Maria (British journal of dermatology, 2013)
Background Lichen sclerosus (LS) is a sclerosing skin disease of presumably autoimmune origin affecting mainly the anogenital area. The aetiology is not completely understood. Comorbidity between genital LS and atopy in girls has been described but so far no controlled study has been performed. Objectives A prospective epidemiological case-control study was designed to clarify if there is comorbidity between genital LS and atopic skin diathesis (AD) in boys. Methods The study included a total of 92 boys aged between 1 and 17 years. The disease group consisted of 48 boys who underwent surgery for phimosis that was histologically confirmed as LS. The control group included 44 boys who were circumcised for phimosis for other medical reasons. Both groups were examined and the parents were interviewed following the criteria of the validated Diepgen atopy score. Patients with a score > 9 were assumed to have AD. Results Within the LS group (median age 8·7 years) 12 boys were diagnosed with AD (25%), while there were only three boys with AD (7%) in the control group (median age 5·3 years). The difference was significant using an age-adjusted logistic regression (P < 0·05). Prior to our study nine boys of the LS group (19%) and four boys of the control group (9%) had already been diagnosed with AD. Conclusions We have demonstrated a significant comorbidity between LS and AD in boys. AD seems to be a priming precondition for the development of LS in boys.
Gesehen am 17.11.2020
First published: 04 August 2012